Utilising CIDOS LMS in technical higher education: the influence of compatibility roles on consistency of use - Ismail, Norhafizah; Ayub, Ahmad Fauzi Mohd; Yunus, Aida Suraya Md; Jalil, Habibah Ab (American Scientific Publishers, 2017)
A remarkable educational phase should consider compatibility of technology use to ensure effective teaching and learning processes. Technical higher education institution has introduced Curriculum Information Document Online System Learning Management System (CIDOS LMS) for Malaysian Polytechnic educators and learners to facilitate the instructional system design, embolden meaning learning and optimise the consistency of use. The present study examines the relationship between compatibility roles among undergraduate engineering students and consistency of use, as well as android game-based learning (GBL) implementation. Previous research has based differences in compatibility on technology utilisation behaviour and found significant differences. One hundred of Year Two undergraduate technical students at Politeknik Merlimau Melaka, Malaysia, took part in the study and completed a survey dealing with compatibility roles, consistency of use and android GBL. The current study shows that compatibility roles, specifically in CIDOS LMS adoption, are the pertinent source of nurturing consistency of use among engineering field students. The findings indicated that compatibility roles have a moderate positive relationship with consistency of use [r = 0.560**; p = 0.01]. Moreover, there is a negative effect between compatibility roles and android GBL [r = −0.001**; p = 0.01]. To sum up, the lecture note obtained the highest percentage (85.8%) among other learning tools used in CIDOS LMS.